Lipoaspirate Shows In Vitro Potential for Wound Healing - Chiara Ceresa; Alessia Borrone; Letizia Fracchia; Maurizio Rinaldi; Alice Marchetti; Carlo Tremolada; Michela Bosetti (MDPI AG, 2022)
Mesenchymal stem cells (MSCs) are a promising therapy in wound healing, although extensive time and manipulation are necessary for their use. In our previous study on cartilage regeneration, we demonstrated that lipoaspirate acts as a natural scaffold for MSCs and gives rise to their spontaneous outgrowth, together with a paracrine effect on resident cells that overcome the limitations connected to MSC use. In this study, we aimed to investigate in vitro whether the microfragmented adipose tissue (lipoaspirate), obtained with Lipogems® technology, could promote and accelerate wound healing. We showed the ability of resident cells to outgrow from the clusters of lipoaspirate encapsulated in a 3D collagen substrate as capability of repopulating a culture of human skin. Moreover, we demonstrated that the in vitro lipoaspirate paracrine effect on fibroblasts and keratinocytes proliferation, migration, and contraction rate is mediated by the release of trophic/reparative proteins. Finally, an analysis of the paracrine antibacterial effect of lipoaspirate proved its ability to secrete antibacterial factors and its ability to modulate their secretion in culture media based on a bacterial stimulus. The results suggest that lipoaspirate may be a promising approach in wound healing showing in vitro regenerative and antibacterial activities that could improve current therapeutic strategies.